Multiscale Materials Modeling. (De Gruyter, 2016)
This book exhibits current approaches to multiscaling in the spatial and temporal domain of materials modeling. The task of deducing properties and behaviours at the device and component level by simulating structures and materials at the atomic and microstructure scales is demonstrated by recent results. These include precipitation, fracture, ferroelectric and magnetoelectric materials as well as biological materials and composites.